TINJAUAN HUKUM ISLAM TERHADAP PERLINDUNGAN HAK-HAK KONSUMEN - Mukhlisin; Fetri Fatorina; Chamid Sutikno (Faculty of Social, Economics and Humanities, 2022)
Trade activities that cause consumerism and the enactment of consumer protection laws in Indonesia cannot be separated because business actors cheat in trade using an economic system that is free of values, norms, and even religious norms, the most important being getting as much profit as possible, the next stage gives birth to a permissive culture, hedonic lifestyle, poverty in the midst of prosperity which is basically contrary to human values ​​and religious teachings. In contrast to the Islamic economic system, which is very contradictory, because it contains religious norms, which as a whole regulate the economic interests of individuals and society. Based on the above, the Islamic economic system prioritizes justice, unity, balance, freedom and responsibility in realizing prosperity for mankind. The approach used in this study is a juridical-normative approach. The method used in analyzing the collected data is the inductive method. The results of the research on the position of Law Number 8 of 1999 concerning Consumer Protection against the rules of Islamic law regarding consumer protection is as a reinforcement of the rules of Islamic law concerning consumer protection in its application in Indonesia. Consumer protection efforts have actually been implied and conceptualized in Islamic rules in every transaction. Then the rules were strengthened and reaffirmed in more detail in the rules of Law Number 8 of 1999 in terms of their application. If the two rules are truly applied to the fullest, it is not impossible for harmony, blessing, profit, protection of the rights of both parties to their respective interests to be achieved.